Academic Senate Minutes 2004-09-02 - Academic Senate:::::::::
Chair's Report. Correspondence. Agenda amended and approved. Minutes of 5/6 & 5/20 approved. Faculty eligible for Emeritus Status Fall 2004 approved. From EPC: Revision of Single Subject Waiver Program in English moved to business. Election of Senators to Executive Committee. Special Reports: WASC update and Green Music Center update. From EPC: Changes in the MBA – First Reading. From EPC: Changes in the Global Studies Program – First Reading. Good of the Order. Resolution in Support of Sonoma State University Associated Students, Inc. Voter Registration, Education and Mobilization Drive approved.